-40-6k=-3(-k+6)+5

Simple and best practice solution for -40-6k=-3(-k+6)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -40-6k=-3(-k+6)+5 equation:


Simplifying
-40 + -6k = -3(-1k + 6) + 5

Reorder the terms:
-40 + -6k = -3(6 + -1k) + 5
-40 + -6k = (6 * -3 + -1k * -3) + 5
-40 + -6k = (-18 + 3k) + 5

Reorder the terms:
-40 + -6k = -18 + 5 + 3k

Combine like terms: -18 + 5 = -13
-40 + -6k = -13 + 3k

Solving
-40 + -6k = -13 + 3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3k' to each side of the equation.
-40 + -6k + -3k = -13 + 3k + -3k

Combine like terms: -6k + -3k = -9k
-40 + -9k = -13 + 3k + -3k

Combine like terms: 3k + -3k = 0
-40 + -9k = -13 + 0
-40 + -9k = -13

Add '40' to each side of the equation.
-40 + 40 + -9k = -13 + 40

Combine like terms: -40 + 40 = 0
0 + -9k = -13 + 40
-9k = -13 + 40

Combine like terms: -13 + 40 = 27
-9k = 27

Divide each side by '-9'.
k = -3

Simplifying
k = -3

See similar equations:

| (2x+10)=(120) | | 26x=180+24-35 | | 2x+2-4=7-2+4 | | A+2(a-5)=320 | | -8(x-1)=6x-6 | | 2.6(t+2)=(1.3t+2)+1.2 | | 4x+4x=90 | | 28-p=5(p-4) | | 2x+3-9=0 | | -6(x-8)=39-3x | | -x+3+12x=-4+4x+49 | | 5y^5-5y^4-10y^3=0 | | -8-5(m+3)=27+5m | | 4x+3=(x-6) | | 12X+26=19X+30 | | 4(p-3)=8(p+5) | | 5t^2+8t-30=0 | | (6x+14)=(8x-24) | | (6x+15)=(8x-24) | | 16X+30=17X+22 | | X-2x^2=15 | | 1.50z=1200 | | 1.50z=2000 | | 0.75z=300 | | 0.75z=1500 | | (x+20)=(2x+10) | | (5b+3)(5b-3)=0 | | 1.50z=1500 | | (x+3)=64 | | (x+40)=(3x) | | -1+5v=5v | | 1.50z=1425 |

Equations solver categories